Abnormal DMSA renal scan findings and associated factors in older children with vesicoureteral reflux - ŞEKERCİ, ÇAĞRI AKIN; KÜTÜKOĞLU, MEHMET UMUT; YÜCEL, SELÇUK; TARCAN, TUFAN; TANIDIR, YILÖREN (SPRINGER, 2021)
Aim There are scanty data on the rate of abnormal Tc-99 m dimercaptosuccinic acid (DMSA) renal scintigraphy and associated factors in children older than 5 years with diagnosis of VUR. We do not have knowledge about which older children should undergo DMSA after VUR diagnosis. This study aims to assess the rate of abnormal DMSA findings and associated factors in children older than 5 years of age diagnosed with VUR. Materials and methods We retrospectively reviewed the medical records of 258 children with VUR diagnosed at or older than 5 year age. 179 children [42 (23.5%) males and 137 (76.5%) females] with complete data were included. 268 reflux units were compared according to gender, bilaterality, grade, reflux phase at voiding cystourethrography, febrile urinary tract infection (fUTI), lower urinary tract dysfunction (LUTD), and DMSA findings with uni- and multivariate analysis. Results The median age was 110 (60-216) months. VUR grades were I, II, and III in 197 (73.6%) units and IV-V in 71 (26.4%). 138 (51.5%) renal units had abnormal DMSA. VUR grade (p < 0.01), unilaterality (p = 0.048), and fUTI (p = 0.031) in univariate but only grade and unilaterality in multivariate analysis are significantly associated with abnormal DMSA. Although reflux at filling phase was predominant in high-grade VUR group, reflux at voiding phase (p = 0.006) in low-medium-grade (1-3) VUR was associated with abnormal DMSA. Conclusion Children older than 5 years of age diagnosed with VUR should be regarded as a high-risk group for abnormal DMSA regardless of gender, unilaterality, grade, reflux phase, fUTI, and LUTD.
Keywords: Vesicoureteral reflux; DMSA; Children; Renal scar; Urinary tract infection; URINARY-TRACT-INFECTION; ANTIBIOTIC-PROPHYLAXIS; PYELONEPHRITIS; MULTICENTER; RESOLUTION; SYSTEM